Achieving high-performance laser welding of SiCp/Al composites for lightweight sports equipment - Hu, Xueqing; Zhao, Wentao; Zhu, Qiang; Wang, Wunian (Frontiers in Materials, 2025)
Lightweight and high strength are key objectives in the development of sports equipment. Although aluminum alloys are still widely used as the primary material, they are limited by relatively low strength and inadequate wear resistance. To further improve the overall performance of sports products, advanced materials are required for their design and manufacture. Silicon carbide particle-reinforced aluminum matrix composites offer a promising alternative due to their high specific strength and stiffness, superior wear and corrosion resistance. These properties make them well-suited for applications demanding lightweight and high-strength characteristics in sports equipment. This study examined the laser welding quality of silicon carbide particle-reinforced aluminum matrix composites fabricated using two distinct methods. The suppression of brittle phases, control of porosity defects, and reinforcement mechanisms at the welded joint were systematically explored through advanced process including continuous laser welding, ultrasonic-assisted laser welding, and the application of active interlayers. It was demonstrated that the continuous laser welding process with addition an active interlayer effectively enhanced molten pool fluidity, thereby minimizing SiC particle burn-off and inhibiting the formation of Al4C3 brittle phases. A joint tensile strength exceeding 80% of the base material was consequently achieved. This research provides an efficient joining technology solution for sports equipment manufacturing, facilitating the broader application of lightweight composite materials in high-end sporting goods.